Enhanced catalytic degradation of amoxicillin by phyto-mediated synthesised ZnO NPs and ZnO-rGO hybrid nanocomposite: Assessment of antioxidant activity, adsorption, and thermodynamic analysis - Amanat Mehwish; Shahzadi Tayyaba; Riaz Tauheeda; Zaib Maria; Nawaz Faisal; Tawfeek Ahmed M.; Khawar Muhammad Ramzan; Park Sung Jea; Choi Dongwhi (Nanotechnology Reviews, 2024)
Antibiotics are resistant compounds that become emerging contaminants that cause hazards to human health and the ecological environment due to their wide production and consumption. The present research reveals the remediation of amoxicillin (AMX) antibiotic by catalytic degradation using fabricated zinc oxide (ZnO) and zinc oxide-reduced graphene oxide (ZnO-rGO) catalysts. The characterization of the catalyst was carried out via UV–Vis spectroscopy, Fourier transform infrared spectroscopy, X-ray diffraction, energy dispersive X-ray spectroscopy, and scanning electron microscopy to evaluate the morphology and composition of synthesised catalyst. The catalytic ability of ZnO-rGO and ZnO was investigated by analysing the degradation of AMX. The ZnO-rGO nanocomposites (NCs) showed improved catalytic performance towards AMX degradation (96%) than pure ZnO nanoparticles (85%), which may be attributed to the incorporation of rGO, which enhanced the adsorption rate and changed the electron–hole recombination rate. The antioxidant potential of synthesised nanomaterials was also analysed by three different methods. The adsorption behaviour was explained through the Langmuir and Freundlich models, and the results revealed that AMX adsorption followed the Freundlich model more closely for both catalysts. The adsorption of AMX was also studied thermodynamically at different temperatures. The negative Gibbs energy change, positive enthalpy change, and entropy change showed the reaction’s spontaneity and endothermic nature. Finally, it can be assumed that the ZnO-rGO NCs could be an effective semiconductor for the degradation of AMX from wastewater.